Prevalence and determinants of opportunistic infections among HIV-infected adults receiving antiretroviral therapy in Ethiopia: A systematic review and meta-analysis - Woldegeorgis, Beshada Zerfu; Zekarias, Zewdineh; Adem, Bulcha Guye; Obsa, Mohammed Suleiman; Kerbo, Amene Abebe (Frontiers in Medicine, 2023)
Background Reliable data on the burden of opportunistic infections (OIs) after the initiation of antiretroviral therapy (ART) is critical for planning health services and reducing OI-related morbidity and mortality. Nevertheless, there has been no nationally representative information on the prevalence of OIs in our country. Therefore, we have undertaken this comprehensive systematic review and meta-analysis to estimate the pooled prevalence, and identify factors associated with the development of OIs in Human Immunodeficiency Virus (HIV)-infected adults receiving ART in Ethiopia. Methods Articles were searched in international electronic databases. A standardized Microsoft Excel spreadsheet and STATA software version 16 were used for data extraction and analysis, respectively. The Preferred Reporting Items for Systematic Reviews and Meta-Analysis (PRISMA) checklist was used to write this report. The random-effect meta-analysis model was used to estimate the pooled effect. The statistical heterogeneity of the meta-analysis was checked. Subgroup and sensitivity analyses were also performed. Publication bias was examined in funnel plots and the nonparametric rank correlation test of Begg and the regression-based test of Egger. Association was expressed through a pooled odds ratio (OR) with a 95% Confidence Interval (CI). Results A total of 12 studies with 6,163 study participants were included. The pooled prevalence of OIs was 43.97% [95% CI (38.59, 49.34)]. Poor adherence to ART [OR, 5.90, 95% CI (3.05, 11.40)], under nutrition [OR, 3.70, 95% CI (2.01, 6.80)], CD4 T lymphocyte count <200 cells /μL [OR, 3.23 95% CI (2.06, 5.07)], and advanced World Health Organization (WHO) HIV clinical stages [OR, 4.84 95% CI (1.83, 12.82)] were determinants of OIs. Conclusion The pooled prevalence of OIs among adults taking ART is high. Poor adherence to ART, under nutrition, a CD4 T lymphocyte count <200 cells /μL, and advanced WHO HIV clinical stages were factors associated with the development of OIs.